2021
DOI: 10.1109/jlt.2020.3024713
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Interrogation of a Chirped FBG Strain Sensor Inscribed in a Multimode Fiber

Abstract: Smartphone-based interrogation of a fiber Bragg grating sensor is, to the best of our knowledge, reported for the first time. The smartphone flashlight LED was used as a light source and a transmissive diffraction grating projected the CFBG spectra on the smartphone camera. In order to efficiently couple light from the smartphone LED to the fiber with CFBG, multimode fiber was used for inscription. Interrogation setup consists of a smartphone and low-cost off-the-shelf available components. Measurement princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…A similar system was reported in [ 11 ] for the interrogation of chirped fiber Bragg grating sensors, inscribed on a multimode fiber for strain and temperature sensing. The chirped grating, with bandwidth ~ 8 nm at the red wavelength, exhibits a wavelength shift that can be detected by estimating the pixel-based spectrum via signal processing.…”
Section: Smartphone Fiber Optic Sensorsmentioning
confidence: 98%
See 2 more Smart Citations
“…A similar system was reported in [ 11 ] for the interrogation of chirped fiber Bragg grating sensors, inscribed on a multimode fiber for strain and temperature sensing. The chirped grating, with bandwidth ~ 8 nm at the red wavelength, exhibits a wavelength shift that can be detected by estimating the pixel-based spectrum via signal processing.…”
Section: Smartphone Fiber Optic Sensorsmentioning
confidence: 98%
“…A different approach was proposed by Markvart et al [ 11 , 106 ], who showed the possibility to interrogate traditional wavelength-selective fiber-optic sensors, such as interferometers [ 106 ] or gratings [ 11 ], using an architecture based on the smartphone. The first system, shown in Figure 12 , is designed for the interrogation of Fabry–Perot (FP) interferometers.…”
Section: Smartphone Fiber Optic Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by the work of Markvart et al that develop a strain sensor based not only on the spectral shift in the guided light created by a fiber Bragg grating using an analysis similar to the one in Pan et al but also manage to characterize it as a temperature sensor. [ 96 ]…”
Section: Optical Temperature Sensors For the Iotmentioning
confidence: 99%
“…With the progress of FBG inscribe technology, many innovative forms of Bragg gratings have been realized, such as chirped FBG [ 16 , 17 , 18 , 19 , 20 ], titled FBG [ 21 , 22 , 23 , 24 ] and phase-shifted fiber Bragg grating (PS-FBG) [ 25 , 26 , 27 , 28 ]. Among them, PS-FBG has attracted extensive attention [ 29 ].…”
Section: Introductionmentioning
confidence: 99%